Utilization of surgical trepan for the obtainment of calvarial autogenous bone graft in maxillary reconstructions - Pereira, Cassiano Costa Silva [UNESP]; Gealh, Walter Cristiano [UNESP]; Martins, Maira Menezes Santos; Homsi, Nicolas [UNESP]; Garcia, Idelmo Rangel [UNESP] (American Academy of Implant Dentistry, 2011)
Maxillomandibular reconstructions are traditionally performed by means of autogenous bone grafts collected from intraoral donor areas and extraoral donor areas such as clavicle, iliac bone, rib, and tibia. The calvarial bone has been studied as an alternative donor area, with a low incidence of complications and minimal postoperative morbidity. Complications such as dural lacerations associated with cerebrospinal fluid leakage and extradural and subdural bleeding were minimized due to the use of surgical trepan, allowing the diploic layer delimitation before the osteotomy, preserving the internal calvarial cortical. The purpose of this article is to suggest a new technique for the obtainment of calvarial bone grafts with surgical trepan.
Keywords: Bone graft; Calvaria; Technique; bone transplantation; craniotomy; human; instrumentation; maxilla; methodology; oral surgery; skull; transplantation; Alveolar Ridge Augmentation; Bone Transplantation; Craniotomy; Humans; Maxilla; Parietal Bone; Tissue and Organ Harvesting